Evaluation of the biological properties of two experimental calcium silicate sealers: an in vivo study in rats - Silva, E. C.A. [UNESP]; Tanomaru-Filho, M. [UNESP]; Silva, G. F.; Lopes, C. S. [UNESP]; Cerri, P. S. [UNESP]; Guerreiro Tanomaru, J. M. [UNESP] (Wiley, 2021)
Aim: To evaluate the biological properties of experimental sealers based on tricalcium silicate and dicalcium silicate, manipulated with polyethylene glycol (CE-1) and with the addition of calcium hypochlorite (CE-2) compared to AH Plus (AHP) and TotalFill BC Sealer (TBC). Methodology: The tissue reaction caused by the materials in the subcutaneous tissue of rats was evaluated after implantation of polyethylene tubes filled with the materials at 7, 15, 30 and 60 days. Sections were stained with haematoxylin and eosin (HE) for morphological analysis and to evaluated number of inflammatory cells/mm2 (ICs). Sections were used for immunohistochemical detection of interleukin-6 (IL-6) and osteocalcin (OC). The von Kossa method was used to identify calcium precipitation in the capsules. The data were submitted to anova and Tukey’s tests, with 5% significance level. Results: At 7 days, CE-1, CE-2 and AHP had higher numbers of ICs. AHP presented higher immunolabelling for IL-6. After 15 days, regarding IL-6, there was no difference between CE-2 and the control group. At 30 days, AHP exhibited the highest number of IC (P < 0.05) and CE-2 and the control group presented the lowest ICs and IL-6-positive cells. After 60 days, all materials exhibited decreases in ICs. CE-2, TBC and the control had the lowest values (P < 0.05). No significant difference was detected between CE-1 and TBC, and between CE-2 and control considering the immunoexpression of IL-6. In this period, AHP had the greatest number of IC and IL-6 (P < 0.05). In all periods, CE-1, CE-2 and TBC sealers had von Kossa-positive structures and OC-immunolabelled cells. CE-2 had higher number of OC-positive cells than the CE-1 and TBC sealers (P < 0.05), in all periods. OC immunolabelling was not observed in the capsules of AH Plus and the control groups. Conclusions: The experimental sealer and its association with calcium hypochlorite, in addition to TotalFill BC Sealer, were biocompatible and had bioactive potential.
Keywords: biocompatibility; calcium silicate; endodontics; immunohistochemistry; root canal filling material